Management of Non-Specific Genital Infections in Infertile Crossbred Cattle - Panchal, MT; Hadiya, KK; Patel, JA; Chaudhari, DV; Bhanderi, BB (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Among 1046 infertile breedable bovines screened in different sexual health camps in and around Anand district during one year, the prevalence of repeat breeding and genital infection was found to be 17.97 and 17.11 %, respectively. The representative 23 HF crossbred infertile cows from within Anand taluka were selected for cultural examination, antibiotics sensitivity of isolates and accordingly, the treatment and pregnancy follow up. The cultural isolation of CVM/genital discharges from 23 crossbred cows revealed bacterial growth in 65.22 (15) % samples; the Gram +ve Bacilli Spp. was prevalent to the highest extent (38.10%; 8) followed by Corynebacterium Spp. (23.81%, 5). All the isolates (100 %) were sensitive to enrofloxacin followed by cefotaxime and tetracycline (73.33% each), while they were resistant to tyrosin. Among the culturally positive cases, use of effective drugs resulted in overall three cycles pregnancy rate of 86.66 (13/15) %, while in culturally sterile cases it was 50 (4/8)%, showing the utility of antibiotics sensitivity testing in managing infertile animals.